Chemical Assistance in Refolding of Bacterial Inclusion Bodies - Alibolandi, Mona (Hindawi Publishing Corporation, 2011)
Escherichia coli is one of the most widely used hosts for the production of recombinant proteins but insoluble expression of heterologous proteins is a major bottleneck in production of recombinant proteins in E. coli. In vitro refolding of inclusion body into proteins with native conformations is a solution for this problem but there is a need for optimization of condition for each protein specifically. Several approaches have been described for in vitro refolding; most of them involve the use of additives for assisting correct folding. Cosolutes play a major role in refolding process and can be classified according to their function as aggregation suppressors and folding enhancers. This paper presents a review of additives that are used in refolding process of insoluble recombinant proteins in small scale and industrial processes.